Scoping Zygomaticomaxillary Complex Fractures With the Eyes of Virtual Reality: Operative Protocol and Proposal of a Modernized Classification. Issue 2 (6th March 2021) - Tel, Alessandro; Sembronio, Salvatore; Costa, Fabio; Robiony, Massimo
Abstract : Supplemental Digital Content is available in the text Abstract : Introduction: Fractures of the zygomaticomaxillary complex (ZMC) represent an extremely heterogeneous group of injuries to the midfacial skeleton. Traditionally, the diagnosis of such fractures was based on 2-dimensional radiograms and, more recently, on volumetric computed tomography (CT) scans, while the treatment was exclusively based on the surgeon's experience. Many classification attempts have been made in the past, but no paper has taken into account the importance of virtual surgical planning (VSP) in proving a modernized classification. The authors propose a classification based on the use of VSP which can guide the surgeon to identify the optimal reduction method and reproduce it in the operating room through the use of navigation. Methods: Patients with ZMC fractures were collected to create a study model. The VSP was used to generate 3-dimensional models of fractures. Fractured segments were duplicated and digitally put in the optimal reduction position. Repositioned fragments were overlapped to their original preoperative counterparts and exported to the surgical navigator to be navigated. Planned virtual reduction was overlaid to postoperative CT scan to assess the accuracy of reduction, explored using color maps and the calculation of root mean square error. Results: For all patients, the application of VSP was successfully accomplished. High accuracy was confirmed between the planned virtual reduction and the postoperative CT scan. A 5-item classification based on VSP is proposed. All patients were included in the presented subclasses. Conclusions: The adoption of virtual planning in ZMC fractures allows for an improved study of the displacement of the fracture and might indicate to the surgeons the required maneuvers to achieve optimal reduction. The presented proposal of classification might be an aid to simplify the choice of the most appropriate reduction method and might provide a deeper insight into the morphologic characteristics of fractures.